Perancangan UI/UX Pada E-Rapor Sekolah Berbabis Prototype Dengan Menggunakan Metode Design Thingking - Ifan renanda dwi putra; Dwi Rosa Indah (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The development of the website at this time can not be separated from computer and information technology. Starting from developing companies, and government agencies, to institutions, but there are problems in these schools, namely, problems with systems that are still manual and teachers want a web design that can be easy to use, has a good design that will be made into a website in the future. website, with the existing problems a prototype design will be made using the Design thinking method, the method used to design a design is the design thinking method which will be combined with the User Experience Questionnaire (UEQ) method used in the testing phase. The result of designing using the design thinking method can produce an interface and improve the user experience as evidenced by measurements using the (UEQ) method which says that of the 6 aspects of the assessment there are 5 excellent aspects (attractiveness, clarity, efficiency, accuracy and novelty) and 1 aspect what is the value of good (stimulation).